Bone health and physical activity through the various life stages - Micklesfield, Lisa (Department of Human Biology, 2024)
The aims of this thesis were to investigate the interaction between physical activity and bone health through various life stages, in order to better understand the determinants of adult bone mass and consequently, osteoporosis. All the studies have been carried out on the various ethnic groups that make up the population of South Africa, with widely divergent economic and sociocultural experiences, and therefore provide us with insight into determinants of bone health within the South African context. In this dissertation, we will explore the relationship and interactions between physical activity, and other lifestyle, physiological and demographic factors, on BMD and bone QUS parameters in the South African population. What sets this thesis apart is that we consider groups that are largely unstudied, groups undergoing demographic and epidemiological transitions, and even groups for whom physical activity may no longer provide protection for bone health.